The Role of Employee Culture Change Management and Transformation in the Competition Success of a Company - Andi Raharjo; Achmad Hidayat Sutawijaya (Clean and Sustainable Production, 2023)
A company is said to be successful if it can survive and grow in its business process. Achieving this certainly requires effort that is not easy for the company. The success of a company in running its business is influenced by many factors. One of the determining factors is how strategic management is implemented in the company. To support the effective operation of strategic management, all employees must understand and implement strategic management comprehensively across all lines. This is what makes companies must be concerned with achieving targets and also developing existing resources, both internal and external resources. PT Hanken Indonesia is a Japanese PMA company engaged in manufacturing. To keep the company surviving in the onslaught of various business climates filled with uncertainties, PT Hanken Indonesia creates a strong and relevant vision and mission for the times. To achieve this vision and mission, the company informs all stakeholders about the company's vision and mission, how to achieve and maintain it. One of them is the company focuses on developing existing human resources by providing training and On Job Training at the workplace. In addition, the company also prepares strategic management to achieve this. With its strategic management, the company hopes to be well realized by all stakeholders, thus the company can continue to grow and develop until now.